A fast estimation procedure for discrete choice random coefficients demand model. Issue 58 (14th December 2017) - Kim, Dong-Hyuk; Song, Yong; Xu, Huaxin
ABSTRACT: We document speed-up gains of graphical processing unit (GPU) computing over central processing unit (CPU) for the estimation of discrete choice random coefficient demand model. When we use a moderate-sized GPU, the computation is six to twenty times faster, where the smallest speed-up factor, six, is obtained from a comparison with the parallel computing over sixteen CPU cores.